Residual stress effects of CMAS infiltration in high temperature jet engine ceramic coatings captured non-destructively with confocal Raman-based 3D rendering. Issue 4 (April 2023) - Stein, Zachary; Naraparaju, Ravisankar; Schulz, Uwe; Tetard, Laurene; Raghavan, Seetha
Abstract: Calcium-magnesium-aluminosilicates (CMAS) are ingested by jet engines and infiltrate into high temperature ceramic coatings during operation. This infiltration increases coating stiffness and promotes coating phase destabilization, encouraging micro-crack formation. Thermomechanical effects from CMAS infiltration were mapped over time with confocal Raman spectroscopy through residual stresses within EB-PVD 7YSZ coatings with microscale resolution. The results show an interplay between physical and chemical components influencing the residual stress. Physical mechanisms influence residual stress more after 1h of infiltration, inducing tensile loading up to 100 MPa on tetragonal ZrO2 Raman bands. Chemical mechanisms impart greater influence after 10h, inducing compressive loading up to 100 MPa. A monoclinic phase volume fraction of about 35% was observed as a transitional point for chemical mechanisms overtaking physical mechanisms in influencing residual stress. These results non-destructively elucidate changes within a coating's residual stress during CMAS infiltration, aiding coating degradation monitoring during maintenance and towards implementing CMAS-mitigation strategies.